802.11 wireless network site surveying and installation - Alexander, Bruce E. (Cisco Press networking technology series., 2005)
The definitive guide to performing wireless network site surveys, selecting the right wireless equipment, and installing 802.11 wireless LANs Prepare for a WLAN installation with this definitive guide Perform a proper site survey to ensure the maximum performance of your 802.11 WLAN Compare and choose the right WLAN technologies to match application and users needs Install WLAN products properly taking the unique needs of the users and environment into account Performing a wireless LAN (WLAN) site survey before installing a wireless network is the key to any successful WLAN deployment. Yet each location and company have unique needs that must be taken into account. 802.11 Wireless Network Site Surveying and Installation helps you understand the challenges associated with any site survey, including multipath mitigation, reflection, absorption, and radio wave interference, plus the added complexity of user and application demands. This book helps you identify obstacles to a successful deployment and guides your equipment decisions to ensure that your WLAN reaches its maximum potential. Use this complete guide to understand the following components of any thorough site survey: The architecture of the access points, cable routes, and electrical needs The proper site survey technique and usage of appropriate utilities The structural and installation obstacles, including building construction, transmission coverage area, building contents, present cable configuration, area regulations, and building codes The documentation that outlines the necessary parts and equipment, and diagrams exhibiting the proper placement of the equipment 802.11 Wireless Network Site Surveying and Installation begins with an introduction to WLAN architectures and definitions and then moves on to site survey methodologies, helping you assess and address your site's specific needs. The book delves into the installation process for WLAN equipment, including the rules and regulations to which WLANs must adhere, various obstacles that arise when installing WLAN equipment, and ways to connect WLAN products to the wired network. 802.11 Wireless Network Site Surveying and Installation is your complete guide to performing a WLAN site survey and successfully installing your 802.11 wireless network. This book is part of the Networking Technology Series from Cisco Press¿ which offers networking professionals valuable information for constructing efficient networks, understanding new te ...